Metabolite production by entomopathogenic fungi - Roberts, Donald W.; Gpta, Sandeep; Leger, Raymond J. ST. (Pesquisa Agropecuaria Brasileira, 1992)
The entomopathogenic fungi produce a wide assortment of metabolites, some of which are important to the host-specialization of this group of fungi. Very few entomopathogenic fungi have been examined in detail for their metabolites and in even fewer cases is there information on the role of these metabolites in the disease process. Nevertheless, it is clear that certain proteases and lipases are crucial to the invasion of insect cuticle by the fungus. These fungi have the unusual ability to hydrolyze branched alkanes. Also, they normally produce very active, broad-spectrum proteases. These are needed for penetration of the hydrophobic epicuticle and the highly pxoteinaceous cuticle of insects. Chitinases also are involved, but usually have only secondary importance as penetration enzymes. The best known of the penetration enzymes is Pr1 - a chymoelastase protease, the major enzymic product of Metarhizium anisopliae infection structures (appressoria). Growth in the hemocoel involves various hydrolytic enzymes; and, in addition, may lead to the formation of smaller compounds with detrimental effects on the host. These can be simple organic poisons, e.g. oxalic acid; but more often they are larger compounds, and many are depsipeptides. Metabolites of entomopathogenic fungi are currently being investigated as potential chemical insecticides and as pharmacological agents.